Pomiar ryzyka portfela z wykorzystaniem funkcji powiązań (copula functions) i teorii wartości ekstremalnych w przypadku dywersyfikacji międzynarodowej - Rokita, Paweł (Wydawnictwo Akademii Ekonomicznej im. Oskara Langego we Wrocławiu, 2005)
This paper addresses the problem of modeling risk of internationally diversified stock portfolios. According to the results of other published researches, it is assumed that the models applied here should allow for fat tails, as well as for non-linear dependence structure. Classical multivariate - normal portfolio model does not fulfill that requirement.Generally speaking, the research carried out here may be divided into two stages. In the first stage series of subsequent one-day Value at Risk (VaR) forecasts are calculated for some chosen portfolios. The following models are used in the calculations:- Archimedean copulas with margins whose tails are approximated using generalized Pareto distribution (extreme-value-theory approach),- Archimedean copulas with normal margins,- the benchmark model: multivariate normal VaR.In the second stage the results of applying aforementioned models are compared using back testing. The VaR-forecasts-testing procedure comprises tests of number and independence of VaR exceedances. (original abstract)
Prace Naukowe Akademii Ekonomicznej we Wrocławiu; 2005; nr 1088, t. 2, s. 191-200